Altered Innate Immune and Glial Cell Responses to Inflammatory Stimuli in Amyloid Precursor Protein Knockout Mice. - Anna Carrano; Pritam Das (PLoS ONE)
Amyloid precursor protein (APP) and its cleaved products have been reported to have important functions in CNS health, including in memory and synapse formation, cell survival and neuroprotection. Furthermore APP and its cleaved products have been shown to be transiently increased in response to various CNS stressors, suggesting a role in response to acute cellular injury. In an attempt to further understand the function of APP in response to CNS injury, we have used intracranial LPS injection as an inflammatory injury model in APP knock out mice (APPKO). Our data show that innate immune responses to LPS injection is significantly blunted in APPKO mice compared to APP sufficient wild type (BL6) mice. Morphologically, glial cells in APPKO mice appear less reactive, with shorter ramified processes and smaller cell bodies in response to LPS. Additionally, quantitative RT-PCR analysis for several glia markers and innate immune cytokine levels (e.g. TNFα, IL-6, IL-1β and IL-10) showed significantly reduced expression levels in LPS injected APPKO mice. In vitro cell culture assays confirmed this attenuated response to LPS stimulation by primary microglial cells isolated from APPKO mice. Our data suggests that APP full length protein and/or its cleaved products are necessary to mount a complete and effective innate immune cell response to inflammatory injury.